Pengaruh Kualitas Produk, Lifestyle, dan Atmosfer Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Intervening - Rif’atul Khusnia; M. Hufron; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of product quality, lifestyle, and atmosphere on consumer loyalty with customer satisfaction as an intervention which is located on Jl. Tenes No.14, Kauman, Klojen District, Malang City, East Java. The method used is quantitative research that aims to explain the position of each variable and its influence between one variable and another. The main method used is by distributing Likert scale questionnaires to respondents who have visited or purchased products at My Kopi-O Indonesian Bistro Malang City. The sample calculation in this study used the Malhotra formula which resulted in 80 respondents. The results of this study, the atmosphere variable has a significant effect on consumer loyalty through customer satisfaction. Keyword : Product Quality, Life style, atmosfer and customer statisfaction